2020
DOI: 10.1016/j.ctro.2020.05.004
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of suboptimal dosimetric coverage of pretherapeutic 18F-FDG PET/CT hotspots on outcome in patients with locally advanced cervical cancer treated with chemoradiotherapy followed by brachytherapy

Abstract: Introduction: Areas of high uptake on pre-treatment 18 F-fluorodeoxyglucose (18 F-FDG) positron emission tomography/computed tomography (PET/CT), denoted as ''hotspots", have been identified as preferential sites of local relapse in locally advanced cervical cancer (LACC). The purpose of this study was to analyze the dosimetric coverage of these hotspots with high dose-rate brachytherapy (BT). Methods: For each patient, a rigid registration of the CT from the pre-treatment PET/CT with the radiotherapy planning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, a great number of studies have also concentrated on the predictive value of PET, and found that pretreatment values or relative changes in PET parameters [69], such as SUVmax and metabolic tumor volume (MTV), were associated with treatment responses and long-term outcomes [70]. Lucia et al found that the high-uptake volume on baseline PET/CT was correlated with the site of recurrence, and suboptimal dosage coverage of the area could be associated with a higher risk of recurrence [71,72]. The investigation of the dose-effect relationship within these PET-based biological target volumes remains a crucial area of research.…”
Section: Pet-guided Bt: On the Waymentioning
confidence: 99%
“…Furthermore, a great number of studies have also concentrated on the predictive value of PET, and found that pretreatment values or relative changes in PET parameters [69], such as SUVmax and metabolic tumor volume (MTV), were associated with treatment responses and long-term outcomes [70]. Lucia et al found that the high-uptake volume on baseline PET/CT was correlated with the site of recurrence, and suboptimal dosage coverage of the area could be associated with a higher risk of recurrence [71,72]. The investigation of the dose-effect relationship within these PET-based biological target volumes remains a crucial area of research.…”
Section: Pet-guided Bt: On the Waymentioning
confidence: 99%